2020
DOI: 10.7189/jogh.10.0101003
|View full text |Cite
|
Sign up to set email alerts
|

More effective strategies are required to strengthen public awareness of COVID-19: Evidence from Google Trends

Abstract: More effective strategies are required to strengthen public awareness of COVID-19: Evidence from Google Trends Background The outbreak of coronavirus disease 2019 (COVID-19) has posed stress on the health and well-being of both Chinese people and the public worldwide. Global public interest in this new issue largely reflects people' s attention to COVID-19 and their willingness to take precautionary actions. This study aimed to examine global public awareness of COVID-19 using Google Trends.Methods Using Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 21 publications
9
107
0
3
Order By: Relevance
“…Google Trends has become a useful tool for monitoring awareness about public health at both national and international levels. It shows a relationship between topics related to COVID‐19 and search volumes (Hu et al, 2020).…”
Section: Introduction: Information Needs During a Pandemicmentioning
confidence: 99%
“…Google Trends has become a useful tool for monitoring awareness about public health at both national and international levels. It shows a relationship between topics related to COVID‐19 and search volumes (Hu et al, 2020).…”
Section: Introduction: Information Needs During a Pandemicmentioning
confidence: 99%
“…It is evident that perceptions and myths such as drinking raw alcohol can cure COVID-19 by people in Iran (7), that 5G towers are the cause for COVID-19 by people in the UK (8), and eating garlic or mint can cure COVID-19, as well as many others (9), can lead to serious damage and may increase the chances of contamination. A recent study has identified that there is a positive correlation between the increase in the number of COVID-19 cases and the relative search volumes of terms related to COVID-19 (10).…”
Section: Introductionmentioning
confidence: 99%
“…The headquarters also used the apps regarding community service to collect and analyze the residents’ needs. From theory to practice, many pieces of evidence showed that it was feasible to research the epidemic situation and the changing trend of community service through a network of public opinion information [ 13 ].…”
Section: Resultsmentioning
confidence: 99%